Implicações de custo financeiro e recursos humanos em assistência odontológica no Brasil segundo o modelo escandinavo Implications in terms of costs and manpower of using the Scandinavian dental care model in Brazil - Jefferson L. Traebert (Universidade de São Paulo, 1996)
Objetivou-se detectar e analisar as implicações em custos e recursos humanos em odontologia de uma hipotética aplicação dos conceitos escandinavos de atenção odontológica no Brasil. Duas sociedades foram escolhidas para serem estudadas: Suécia, país da Escandinávia, e Santa Catarina, Estado da região Sul do Brasil. A análise teórica dessas implicações foi realizada a partir da determinação das necessidades de recursos humanos em odontologia, considerando-se os altos índices de doenças bucais no Estado brasileiro. Utilizou-se o programa de software "Health Through Oral Health" da Organização Mundial da Saúde-Federação Dentária Internacional (1989). Os resultados mostraram alto custo financeiro e a necessidade de se aumentar em até 85% o recurso humano disponível para atuar em saúde bucal no Estado de Santa Catarina. Concluiu-se que os princípios de alta provisão de recursos humanos e financeiros, característicos do modelo escandinavo, não serviriam para serem adotados por Santa Catarina e, extensivamente, pelo Brasil. The implications in terms of dental manpower and costs of applying the Scandinavian system of dental care in Brazil are specified and analysed. Two societies were chosen for study: those of Sweden, in Scandinavia and Santa Catarina, State in southern Brazil. The theoretical analysis of the implications was undertaken on the basis of an estimate of dental and auxiliary manpower required to deal with the high levels of oral disease and needs (caries, teeth needing extraction, periodontal diseases and the need for full dentures) in Santa Catarina. This estimate was undertaken by means of the World Health Organization-Fédération Dentaire Internationale (WHO-FDI) Model "Health Through Oral Health" (1989). The implications in costs, taking the total Swedish expenditure per dentist as a basis, were calculated and applied to the manpower calles for by the WHO-FDI model. The high costs resulting showed that the application of the Swedish model of dental care to Santa Catarina would be unrealistic. The implications in terms of manpower were calculated by applying the manpower ratios considered desirable in Sweden to Santa Catarina. In order to achieve the Swedish dentist: population ratio, Santa Catarina would need 85% more dentists that it had in 1990. Regarding auxiliary personel, the Brazilian State of Santa Catarina would need to train a larg number of new personnel in order to attain the Swedish auxiliary: dentist ratio. In the ligth of the findings of this study, the adoption of the Swedish model of providing dental care by Santa Catarina in terms of costs and manpower is not feasible. Therefore, alternative approaches for the improvement of oral health in Santa Catarina and in the rest to Brazil should be sought. These approaches should take consider political, cultural and socio-economic aspects of Brazilian society into consideration.